MEKANISME SEKRESI ENZIM PENCERNAAN DI PANKREAS MANUSIA - Adinda Tosifa Kemit; Rido Riyan Dani; Anisa Fitrah Azkia; Nurul Sakinah; Elza Yusna Nasution; Irfan Sazali Nasution (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Abstract. The pancreas is a vital organ in the human digestive system, which has exocrine and endocrine functions. Its exocrine function involves the production and secretion of important digestive enzymes such as amylase, lipase, and protease, which are crucial for the digestion of carbohydrates, fats, and proteins. This research uses a qualitative approach with a literature study method. This approach was chosen to enable an in-depth understanding of the mechanisms of digestive enzyme secretion in the pancreas through analysis and synthesis of information from the available literature. The aim of this study was to investigate in detail the mechanisms of digestive enzyme secretion in the human pancreas. Through a literature study approach, this research aims to identify the biochemical and physiological processes involved in the production and secretion of enzymes, consider the factors that influence these processes, and explore their health implications. The results of the analysis show that enzyme production in the pancreas involves a synthesis process in the acinar cells, with the important role of ribosomes, rough endoplasmic reticulum, and the Golgi apparatus. Regulation of enzyme secretion is influenced by hormones and nervous regulation, as well as nutrient interactions. The process of exocytosis, which involves vesicular transport and fusion of vesicles with membranes, is the main mechanism for enzyme release. This research provides a deeper understanding of the mechanism of digestive enzyme secretion in the pancreas.